Assessment of metabolic variability and diversity present in leaf, peel and pulp tissue of diploid and triploid Musa spp. - Drapal, M.; Amah, D.; Schöny, H.; Brown, A.; Swennen, Rony L.; Fraser, P.D. (Elsevier, 2020)
Banana (Musa spp.) plants produce many health promoting compounds in leaf, peel and pulp. For a robust metabolic analysis of these tissues, leaf at five developmental stages were compared to assess suitable sampling practices. Results confirmed that the common sampling practise of leaf 3 is applicable for metabolic comparisons. The developed work flow was applied to analyse the metabolite diversity present in 18 different Musa varieties, providing baseline levels of metabolites in leaf, peel and pulp tissue. Correlation analysis was then used to ascertain whether similar trends can be detected in the three plant tissues of the diversity panel. The genome group displayed a dominant role in the composition of the metabolome in all three tissues. This led to the conclusion that a correlation between tissues was only possible within a genome group as the different parental backgrounds caused too great a variation in the metabolomes. It also suggests the metabolome could be used to monitor the interaction/hybridisation of genomes during breeding programmes.